Escherichia coli O88 induces intestinal damage and inflammatory response through the oxidative phosphorylation and ribosome pathway in Pekin ducks - Li, Chong; Li, Shuzhen; Liu, Jinmei; Cai, Huiyi; Liu, Guohua; Deng, Xuejuan; Chang, Wenhuan (Frontiers in Cellular and Infection Microbiology, 2022)
Colibacillosis is one of the major health threats in the poultry industry worldwide. Understanding the pathogenic mechanisms involved in Escherichia coli-induced inflammatory response may lead to the development of new therapies to combat the disease. To address this, a total of 96 1-day-old male lean Pekin ducklings were employed and randomly allocated to two treatments, each with six replicates of eight ducks. Ducks in the experiment group (EG) and the control group (CG) were separately orally administered with 0.2 ml of pathogenic E. coli O88 (3 × 109 CFU/ml) or equivalent volumes of 0.9% sterile saline solution on day 7, two times with an 8-h interval. Serum and intestinal samples were collected on days 9, 14, and 28. Results showed that ducks challenged with E. coli had lower average daily gain and higher feed intake/weight gain during days 9–14 and overall (P < 0.05). Histopathological examination showed that E. coli decreased the villus height and the ratio of villus height/crypt depth in the jejunum (P < 0.05) on days 9 and 14. The intestinal barrier was disrupted, presenting in E. coli ducks having higher serum DAO and D-LA on days 9 and 14 (P < 0.05) and greater content of serum LPS on day 9 (P < 0.05). Escherichia coli infection also triggered a systemic inflammatory response including the decrease of the serum IgA, IgM, and jejunal sIgA on day 14 (P < 0.05). In addition to these, 1,062 differentially expressed genes were detected in the jejunum tissues of ducks by RNA-seq, consisting of 491 upregulated and 571 downregulated genes. Based on the KEGG database, oxidative phosphorylation and the ribosome pathway were the most enriched. These findings reveal the candidate pathways and genes that may be involved in E. coli infection, allow a better understanding of the molecular mechanisms of inflammation progression and may facilitate the genetic improvement of ducks, and provide further insights to tackle the drug sensitivity and animal welfare issues.